Examining the impact of learning motivation, desire to work, and curiosity of students in the post-COVID-19 pandemic era - Syukur, Yarmis; Afdal, Afdal; Fikri, Miftahul; Zahri, Triave Nuzila; Anggraini, Osy Khalisyah (Intelektual Pustaka Media Utama, 2025)
This research aims to examine the influence of learning motivation based on environmental conditions, desire to work, and main desires. To achieve this, a quantitative research design was used, and a total of 500 students (101 boys and 399 girls) in Indonesia were selected as respondents using proportional random sampling techniques. Data collection was carried out using a learning motivation scale questionnaire. The results showed that students had a high level of motivation, with an average score of 50.8. The desire to work can be seen from hopes and dreams, as well as a conducive environment. It is known that external factors such as encouragement from others and involvement in activities have a greater influence with significance scores of 0.801 and 0.766 respectively. Meanwhile, appreciation and hopes or aspirations each received a score of 0.709 and 0.704. This implies that encouragement and activity can be integrated into the student's self. The research also shows that gender does not have a significant effect on the desire to learn. However, providing appropriate encouragement and rewards will increase students' willingness to learn, which can be maintained by educational institutions and parents and instill a desire for personal progress and development.